Self-reported crime rates of women prisoners - English, Kim (Journal of quantitative criminology, 1993)
This paper presents findings from the first study of female prisoners' self-reports of criminal activity. Using the criminal career paradigm to frame the analysis, self-reported estimates of crime participation and frequency rates were examined for eight felony crimes. Important similarities between women and men were found in overall patterns of crime. Specifically, a small proportion of both women and men described committing a large portion of the total crimes reported. These data also suggest that women and men are similar in violent crime participation — a finding that varies from the current literature. Once active in a crime type, women and men committed assault, theft, and forgery at significantly different rates; no gender differences were found in the annualized frequency rates of burglary, robbery, motor vehicle theft, fraud, and drug dealing. However, although statistical differences were not found in the overall frequency of drug dealing, specific patterns of drug dealing reflected considerable gender variation, with a larger proportion of the female sample committing very frequent (daily) drug dealing activity. The findings reflect the value of the criminal career paradigm for the study of gender differences. Future research should include largescale quantitative designs that allow detailed analyses of correlates of the distinct criminal career dimensions.